2019
DOI: 10.1177/1464884919869994
|View full text |Cite
|
Sign up to set email alerts
|

Journalists’ level of knowledge on empirical research and opinion polling: A study of Kenyan journalists

Abstract: This study examines the level of knowledge of Kenyan political reporters on a few key concepts of empirical research and opinion polling. Although data from this study are from a nonrepresentative sample, it offers important insights into levels of knowledge on an important topic in journalism. Results indicate that 63.4 percent of the reporters did not know that survey findings from a nonrandom or nonprobability sample cannot be generalized to the population. Another 63.4 percent did not know that sampling er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…According to Cheruiyot, Baack, and Ferrer-Conill (2019), the difference could stem from data journalism being underdeveloped in African media markets as compared to in the studied Western media markets. Similarly, in Kenya, Kiambi (2019) found that the lack of knowledge on statistics among Kenyan journalists is related to several characteristics of the Kenyan media system, such as government control of the media, commercialization, and limited resources. This special issue also contains two studies with a Western context.…”
Section: Journalistic Cultures Media Markets and The Political Environmentmentioning
confidence: 99%
“…According to Cheruiyot, Baack, and Ferrer-Conill (2019), the difference could stem from data journalism being underdeveloped in African media markets as compared to in the studied Western media markets. Similarly, in Kenya, Kiambi (2019) found that the lack of knowledge on statistics among Kenyan journalists is related to several characteristics of the Kenyan media system, such as government control of the media, commercialization, and limited resources. This special issue also contains two studies with a Western context.…”
Section: Journalistic Cultures Media Markets and The Political Environmentmentioning
confidence: 99%
“…Notably, in Tanzania, media have only analyzed immediate public reaction to polls. Moreover, they have been accused of not sufficiently analyzing poll results before disseminating them (Kiambi, 2021). This means that there are frequent allegations and denials over whether polls accurately reflect the opinions and expectations of the general public (Mutahi, 2008).…”
Section: Introductionmentioning
confidence: 99%